Modeling of telecommunication system wich provide Video-on-Demand service by using of multilayer graph - Агеев, Дмитрий Владимирович; Игнатенко, Артем Анатольевич; Хайдара, Абдалла (Eastern-European Journal of Enterprise Technologies, 2012)
The method of describing of telecommunications systems providing Video-on-Demand service using multi-layer graph is considered in this article. The relations between the structural elements at each hierarchical level of the multi-layer graph are described in the paper